Alternative Splicing and Subfunctionalization Generates Functional Diversity in Fungal Proteomes - Marshall, Alexandra N. (Public Library of Science, 2013)
Alternative splicing is commonly used by the Metazoa to generate more than one protein from a gene. However, such diversification of the proteome by alternative splicing is much rarer in fungi. We describe here an ancient fungal alternative splicing event in which these two proteins are generated from a single alternatively spliced ancestral SKI7/HBS1 gene retained in many species in both the Ascomycota and Basidiomycota. While the ability to express two proteins from a single SKI7/HBS1 gene is conserved in many fungi, the exact mechanism by which they achieve this varies. The alternative splicing was lost in Saccharomyces cerevisiae following the whole-genome duplication event as these two genes subfunctionalized into the present functionally distinct HBS1 and SKI7 genes. When expressed in yeast, the single gene from Lachancea kluyveri generates two functionally distinct proteins. Expression of one of these proteins complements hbs1, but not ski7 mutations, while the other protein complements ski7, but not hbs1. This is the first known case of subfunctionalization by loss of alternative splicing in yeast. By coincidence, the ancestral alternatively spliced gene was also duplicated in Schizosaccharomyces pombe with subsequent subfunctionalization and loss of splicing. Similar subfunctionalization by loss of alternative splicing in fungi also explains the presence of two PTC7 genes in the budding yeast Tetrapisispora blattae, suggesting that this is a common mechanism to preserve duplicate alternatively spliced genes.